LEGAL POSITION OF FIDUCIARY DEEDS IN A MURABAHA CONTRACT FOLLOWING THE INDONESIAN CONSTITUTIONAL COURT DECISION NUMBER 18/PUU-XVII/2019 ON DEFAULT AGREEMENT BY CREDITORS AND DEBTORS - Arifah, Risma Nur; Fidhayanti, Dwi (Jurisdictie: Jurnal Hukum dan Syariah, 2021)
This normative research aims at analyzing the legal position of fiduciary deeds in murabaha contract following the decision of Indonesian Constitutional Court No. 18/PUU-XVII/2019 on default agreement between creditors and debtors. The study applied conceptual and statute approaches. The results reveal that the fiduciary deed position after the mentioned decision is about the existing agreement carried out as it should. While for the fiduciary deed implemented after the decision exists, there must be a default agreement as a form of the decision’s implementation and anticipation if in the future the debtor does not voluntarily turn in the fiduciary object. Efforts to draw up an agreement on the clause of default in a fiduciary deed with murabaha financing in Islamic banking is part of preventive legal protection. Legal protection is an effort made by law enforcement to protect the rights of legal subjects. Default may not be declared unilaterally by the creditor. Execution of court decisions that have legal force must still be carried out, if at the beginning, there is no agreement regarding a breach of contract and when there is a default but the debtor refused to voluntarily submit the collateral.Penelitian ini merupakan penelitian hukum normatif dengan tujuan untuk menganalisis kedudukan hukum fidusia dalam akad murabahah pasca Putusan Mahkamah Konstitusi Republik Indonesia Nomor 18/PUU-XVII/2019 tentang wanprestasi antara kreditur dan debitur. Penelitian ini menggunakan pendekatan perundang-undangan dan pendekatan konseptual. Hasil penelitian menunjukkan bahwa kedudukan akta fidusia setelah putusan tersebut tentang perjanjian yang ada dilaksanakan sebagaimana mestinya. Selanjutnya, untuk akta fidusia yang dilaksanakan setelah putusan ada, harus ada kesepakatan wanprestasi sebagai bentuk pelaksanaan putusan dan antisipasi jika di kemudian hari debitur tidak menyerahkan benda fidusia secara sukarela. Upaya penyusunan kesepakatan klausula wanprestasi dalam akta fidusia dengan pembiayaan murabahah di perbankan syariah merupakan bagian dari perlindungan hukum preventif. Perlindungan hukum merupakan upaya yang dilakukan oleh penegak hukum untuk melindungi hak-hak subyek hukum. Wanprestasi tidak dapat dinyatakan secara sepihak oleh kreditur. Eksekusi putusan pengadilan yang telah berkekuatan hukum tetap harus dilaksanakan apabila belum ada kesepakatan mengenai wanprestasi di awal. Hal ini juga berlaku apabila terjadi wanprestasi, tetapi debitur menolak untuk menyerahkan agunan secara sukarela.